Pemanfaatan Teknologi Ecoprint Busana Modern sebagai Upaya Pelestarian Lingkungan dan Peningkatan Pendapatan Masyarakat di Kelurahan Tanah Merah Kota Samarinda - Mika Debora Br Barus; Ahmad Zamroni; Mujibu Rahman; Adnan Putra Pratama; Farida Aryani; Muhammad Rizqy Septyandy; Andi Baso Sofyan A. P.; Dito Aditia Darma Nasution (Jurnal Surya Masyarakat, 2024)
Ecoprint techniques have shifted to dyeing and patterning textiles. Ecoprint is a dyeing process that forms an image on fabric using leaf structures and produces patterns. This community empowerment activity aims to increase the knowledge and competence of mothers in Tanah Merah Subdistrict, Samarinda City, by using new Ecoprint technology to protect the environment and increase community income, implementing the activity through persuasive teaching methods with stages of preparation, coordination, implementation and assessment. The activity results show that 1) the knowledge of housewives in Tanah Merah Subdistrict, Samarinda City, has increased about using natural dyes in plants that are good to buy through ecoprint. 2) Increasing the awareness of housewives in Tanah Marah Subdistrict, Samarinda City, about transforming plants into natural dyes using primissima mori cloth as a creative project. 3) Increasing the knowledge and work of housewives in Tanah Merah Subdistrict, Samarinda City, regarding the processing and production environment using natural dyes. With the results of this activity, it is hoped that it can protect the environment and increase community income.